Influence of body mass index on long-term outcome in patients with rectal cancer-a single centre experience - Kalb, Maximilian; Langheinrich, Melanie C.; Merkel, Susanne; Krautz, Christian; Brunner, Maximilian; Bénard, Alan; Weber, Klaus; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (Cancers, 2019)
Background: Excess bodyweight is known to influence the risk of colorectal cancer; however, little evidence exists for the influence of the body mass index (BMI) on the long-term outcome of patients with rectal cancer. Methods: We assessed the impact of the BMI on the risk of local recurrence, distant metastasis and overall-survival in 612 patients between 2003 and 2010 after rectal cancer diagnosis and treatment at the University Hospital Erlangen. A Cox-regression model was used to estimate the hazard ratio and multivariate risk of mortality and distant-metastasis. Median follow up-time was 58 months. Results: Patients with obesity class II or higher (BMI ≥ 35 kg/m2, n = 25) and patients with underweight (BMI < 18.5 kg/m2, n = 5) had reduced overall survival (hazard ratio (HR) = 1.6; 95% confidence interval (CI) 0.9-2.7) as well as higher rates of distant metastases (hazard ratio HR = 1.7; 95% CI 0.9-3.3) as compared to patients with normal bodyweight (18.5 ≤ BMI < 25 kg/m2, n = 209), overweight (25 ≤ BMI <30 kg/m2, n = 257) or obesity class I (30 ≤ BMI >35 kg/m2, n = 102). There were no significant differences for local recurrence. Conclusions: Underweight and excess bodyweight are associated with lower overall survival and higher rates of distant metastasis in patients with rectal cancer.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Body mass index; Distant metastasis; Overall survival; Rectal cancer